COLORADO RIVER COMPACT ENTITLEMENTS, CLEARING UP MISCONCEPTIONS (Utah Environmental Law Review; Vol 28 No 1 (2008))
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 st1\:*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} I was pleased to speak at the Stegner Symposium in March of 2007 about misconceptions surrounding the Colorado River Compact.   This article documents and expands upon my oral presentation at the symposium.   The misconceptions I address include these:   (1) the 1922 Colorado River Compact Commissioners based the compact on mistaken hydrology; (2) they did not account for Native American water rights or the Republic of Mexico’s use of the river; (3) the compact is in need of revision; and (4) Lake Powell should be decommissioned. In my view, these misconceptions fail to recognize historical events surrounding the compact’s formation.   More fundamentally, they ignore the legal context and effect of the compact, as well as the many acts of Congress that implement both the 1922 Colorado River Compact and the 1948 Upper Colorado River Basin Compact.   We do well to remember why the 1922 and 1948 compacts exist and what great accomplishments they continue to be.